2019
DOI: 10.1111/odi.13105
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a newly developed mouth gel for xerostomia relief—A randomized double‐blind trial

Abstract: Objectives To determine the efficacy of a new symptom‐relieving mouth gel vs. a widely used control gel on xerostomic burden. Materials and methods This randomized, double‐blind, crossover trial investigated the efficacy of the test gel (Dr. Wolff Gel) vs. control (Biotene) in participants with xerostomia (n = 32; mean age 60 years). Oral examinations were taken at baseline, and xerostomic visual analogue scales (xVAS), after‐use questionnaires and willingness to pay were investigated before and after use. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
3
8
0
1
Order By: Relevance
“…We agree with Barbe et al [ 36 , 37 , 38 ] on the importance of the patients’ perspective that providing symptomatic relief is only one part of the whole treatment concept. The treatment of xerostomia should not only include symptom relief, but it should be incorporated into a whole diagnostic, prevention and treatment concept that also addresses the causes of dry mouth and its influence on general health conditions and on oral health and quality of life.…”
Section: Discussionsupporting
confidence: 90%
“…We agree with Barbe et al [ 36 , 37 , 38 ] on the importance of the patients’ perspective that providing symptomatic relief is only one part of the whole treatment concept. The treatment of xerostomia should not only include symptom relief, but it should be incorporated into a whole diagnostic, prevention and treatment concept that also addresses the causes of dry mouth and its influence on general health conditions and on oral health and quality of life.…”
Section: Discussionsupporting
confidence: 90%
“…The finding that oil pulling significantly improved the subjective burden of medication-induced xerostomia is of importance. Other studies by our group, which examined commercial over-the-counter (OTC) products such as mouth gels for symptom relief in populations with the same inclusion criteria, study design and endpoints, have shown less convincing or similar results regarding the overall xerostomic burden (Barbe et al, 2017(Barbe et al, , 2019. Since recommendations state that the treatment of subjective xerostomia should remain mainly symptomatic due to the lack of causal therapies (Villa et al, 2015;Wolff et al, 2017), oil pulling should be considered when advising patients.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of this study were the parallel-group randomized controlled design and the long duration of 2 months, which provide a high level of evidence for clinical practice. To date, only a few randomized controlled trials have been conducted to investigate the effects of artificial saliva on oral health, and most studies used a crossover design and of shorter duration [24,37,49]. Moreover, the dry mouth characteristics of the participants were quite similar because we only included xerostomic patients due to definitive radiotherapy, which usually leads to severe hyposalivation.…”
Section: Discussionmentioning
confidence: 99%